Why do some Australian onychophorans have fantastic heads? - Monge, Julián (2019)
Males of some Australian onychophorans transfer their spermatophores with spectacular structures in their head, such as pits with palps and spines. No one has explained why these structures allow this species to be identified. Here we propose that, when its head is the genital apparatus, natural selection treats it as a genital apparatus. Probably these fantastic heads of Australian onychophorans are just another case of divergent sexual evolution by sexual selection.